Antagonistic Activity of Endophytic Bacillus Species Against Colletotrichum Gloeosporioides for the Control of Anthracnose Disease in Black Pepper (Piper Nigrum L.) - Yap, Chin Ann; Awang Ahmad Sallehin, Awang Husaini; Hairul, Azman Roslan; Mohd Hasnain, Hussain; Samuel, Lihan (Researchgate, 2015)
Anthracnose caused by Collectotrichum gloeosporioides is a serious disease of black pepper. The antagonistic effect of three Bacillus species, i.e. Bacillus strain CBF, YCA0098 and YCA5593, were tested against Collectotrichum gloeosporioides in vitro and in vivo. In vitro test showed that all Bacillus species significantly reduce the mycelia growth and spore germination of the C. gloeosporioides. Scanning electron microscopy revealed significant inhibition of C. gloeosporioides spore germination on pepper leaves surface. Combination of bacterial strain CBF, YCA0098 and YCA5593 maintained but not increased the inhibitory effect on spore germination of C. gloeosporioides when cells were co-incubated with C. gloeosporioides and when the pathogen was incubated in mixture of cell-free culture extracts. Combination of strains maintained efficacy in control of C. gloeosporioides in pepper vines compared to individual strains, but reduced variability and improved consistency between experiments, especially mixture of strain CBF, YCA0098 and YCA5593.